KOMUNITAS ISLAM DIGITAL: IDENTITAS SOSIAL DAN PERUBAHAN ABAD KE-21 - Sauri, Muhammad Sofyan; FARHAH, FARHAH (Mozaic: Islamic Studies Journal, 2024)
This paper examines the role of digital Islamic communities in shaping social identity and promoting social change in the modern era. Through an analysis of various platforms, including online forums, social media, and educational portals, the research highlights how virtual spaces enable Muslims worldwide to connect and share. These communities serve not only as channels for discussing issues relevant to Islamic values, such as social justice and cultural cohesion, but also as tools for advocating social change. Furthermore, the paper discusses how digitalization has transformed religious learning and influenced Islamic thought in the online context. Online communities contribute to the evolution of thinking by providing spaces for more inclusive and participatory dialogue. The research finds that the existence of digital Islamic communities is crucial in creating a new collective awareness and identity that transcends geographical boundaries, thereby fostering networks of solidarity among the global Muslim community. Thus, this paper emphasizes the importance of digital platforms in facilitating social interaction and encouraging activism in contemporary contexts.